Exploring Integrated Reporting and Firm Value: Evidence from Global Research Trends - Himmatul Ulya Dynopha; Taufiq Arifin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the development of research on integrated reporting (IR) and firm value through a Systematic Literature Review (SLR) approach and bibliometric analysis of Scopus-indexed articles published between 2015 and 2025. A total of 81 articles were analyzed using VOSviewer software to identify publication trends, dominant theories, influential journals, the most productive countries, author collaboration networks, and keyword co-occurrence patterns. The findings indicate that research on integrated reporting and firm value has grown significantly, particularly after 2020, in line with increasing global attention to sustainability, ESG, transparency, and long-term value creation. Agency theory, signaling theory, stakeholder theory, and legitimacy theory emerged as the most dominant theoretical foundations employed in previous studies. The bibliometric analysis also revealed strong relationships among the keywords integrated reporting, firm value, sustainability, corporate governance, and value relevance, reflecting the multidisciplinary nature of this research topic. Empirically, most studies demonstrate that integrated reporting positively affects firm value through improved information disclosure quality, reduced information asymmetry, and enhanced investor confidence, although inconsistent findings remain across different regulatory environments and firm characteristics. This study contributes by providing a comprehensive overview of the intellectual structure and research development of integrated reporting and firm value, while also offering practical implications for companies, policymakers, and researchers in supporting sustainable corporate value creation.